Racial Conditions : Politics, Theory, Comparisons - Winant, Howard (Book collections on Project MUSE., 1994)
More than a quarter-century after the passage of civil rights legislation in the United States and decades since the last European colonies attained their independence, race continues to play a central role in cultural, political, and economic life, both in the United States and around the globe. Howard Winant argues that race cannot be understood as a "social problem" or as a "survival" of earlier, more benighted ages